Comparative proteomics analysis indicates that palmatine contributes to transepithelial migration by regulating cellular adhesion. (1st January 2020) - Hui, Wang; Feng, Yang; Baoqi, Yan; Shuwei, Dong; Ruihua, Xin; Jiongjie, He; Dongan, Cui; Yan, Sun; Shidong, Zhang; Zuoting, Yan
Abstract: Context: Palmatine, a biologically active isoquinoline alkaloid, possesses multiple pharmaceutical activities against mucosal infection and inflammation. Objective: There are no reports about the influence of palmatine on uterine mucosal epithelial cells. Materials and methods: We used proteomics to analyse differentially expressed proteins (DEPs) in goat endometrial epithelial cells (EECs) stimulated by lipopolysaccharide (LPS, 5 μg/mL, the dosage can induce inflammatory response, according to our previous study) for 12 h and then treated with palmatine (80 μg/mL) for 8 h; the dosage was selected based on MTT assay. The EECs without any treatment were used as controls. Every group was treated in triplicate. Results: A total of 428 DEPs in LPS-stimulated group and 486 DEPs in the palmatine-treated group were identified. Functional annotation analysis showed that palmatine mainly regulated the protein expression of structural molecules involved in the response to stimuli. Pathway analysis showed that cell adhesion molecule (CaM) pathways were most significant enriched due to palmatine treatment. Junction adhesion molecule 1 (JAM1), nectin 1 (NECT1) and cadherin 5 (CDH5), which play important roles in the transepithelial migration (TEpM) of leukocytes, were significantly downregulated by palmatine. Meanwhile, other proteins essential to the maintenance of cell adhesion and those that facilitate leukocyte migration were upregulated after palmatine treatment. Discussion and conclusions: The results suggested that palmatine regulates the expression of CaMs to affect TEpM during uterine mucosal inflammation and provides novel insight to understanding and developing palmatine pharmacology. Palmatine is a promising drug for treatment of mucosal inflammation.